Kecepatan Pelaporan Berbasis Sistem Informasi dan Pemeriksaan Manual Sesuai Standar Pelayanan Kementerian Kesehatan - Sa'adah Mujahidah; Melyana Nurul Widyawati (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2019)
The purpose of this study was to see and find out the differences in the speed of information-based reporting systems with manual inspection according to the Ministry of Health service standard procedures. This research is a quantitative research with quasy experimental research design using posttest only with control group design. The results showed that there was a difference in reporting time between reporting based on information systems with manual reporting on postpartum mothers with examinations according to the Ministry of Health standards with a p-value of 0,000 (<0.005). In conclusion, web-based information systems accelerate the reporting time of postpartum maternal health services compared to manual checks according to the Ministry of Health's service standards. Keywords: Postpartum, Speed, Information Systems, Time Reporting